AqGRISI - A novel online framework for aquatic genetic resource information system to support national and global biological diversity commitments - Ajey Kumar Pathak,; Rajesh Dayal,; Iliyas Rashid,; Rejani Chandran,; Poonam Jayant Singh,; Reeta Chaturvedi,; Rameshwar Pati,; Ravi Kumar,; Vindhya Mohindra,; T. T. Ajith Kumar,; Rajeev Kumar,; Joykrushna Jena ,; et al. (Indian Journal of Fisheries, 2025)
This article presents the development of an online information system for aquatic genetic resources of India named, Aquatic Genetic Resource Information System of India (AqGRISI). The system is designed with integrated data and user management capabilities. The growing importance of online information systems in management of the biological diversity and agrobiodiversity has invited attention of the researchers to make such information publicly accessible through digital platforms. AqGRISI is developed as a concept framework and validated for use and is presently accessible at URL: https://aqgrisi.nbfgr.res.in/#/. It is designed to manage compiled data from authenticated published sources, using a database management system and programming for online  information presentation. It ensures accessibility through web technologies within the Windows operating environment. The system will provide comprehensive information of the fish species, from a single page, covering various aspects such as biology, distribution, taxonomy and type specimens. The database is integrated with information from in-house databases such as HRGFish, FMiR, FBIS, FishKaryome, and FishMicrosat along with patent information. Additionally, AqGRISI is linked to other nationally and internationally significant online resources and serves as a repository for fish accessions preserved in the National Fish Museum and Repository. It includes data on cell lines and facilitates the intake of information on the voucher specimens, cryopreserved sperm accessions and tagged fish species maintained at live germplasm resource centers of ICAR-National Bureau of Fish Genetic Resources. AqGRISI is enriched with dynamic digital maps featuring geospatially tagged type specimens with details on species occurrence. These type specimens are also linked to the National Museum of Natural History, Paris, France, allowing users to access images of holotypea, syntypea, paratypes and neotypes along with relevant taxonomic information. Among the available online resources on aquatic animals, AqGRISI envisages to serve as a centralised platform providing researchers, academicians, managers, planners and other stakeholders, with a single-point access to information on fish species. Currently the system is validated for information on finfish species; however, future expansions will enable customisation of this conceptual framework to include other components of aquatic biodiversity, such as shellfish, seaweeds and more. The concept framework also holds the possibility for usage by other countries especially in Asia, which share ancestral aquatic gene pools. Keywords: Aquatic Genetic Resource Information System, Database, Fish, India